CORN CUSTOMER SATISFACTION LEVEL IN THE LAMONGAN AREA - Muhammad Chusnul Khitam (Jurnal Scientia, 2023)
The unstable increase in the price of shallots during the holidays causes consumers to experience dissatisfaction. The aims of this research is to analyze the effect of price increases, seller friendliness, ease of access and product quality on customer satisfaction. The research method used quantitative approach using a survey method with a sample of 100 respondents who had purchased shallots. The data analysis methods used multiple liner regression, multiple correlation, coefficient of determination, t test and F test. The research results show that price increases, seller friendliness and ease of access have a positive and significant influence. Meanwhile, product quality does not have a significant relationship with customer satisfaction. This study underlines that price increases have the most dominant influence on customer satisfaction. Meanwhile, the seller's friendliness and ease of access are effective stimulus in increasing customer satisfaction.